Management of an Unusual Ectopic Eruption of Maxillary Canine - Aileni, Kaladhar Reddy (J Clin Diagn Res, 2017)
Transposition of teeth is a rare condition, with a prevalence of 0.3-0.4% in general population. They are more commonly observed in females, and may occur unilaterally/bilaterally with greater frequency of left side occurrence in unilateral transposition cases. A 17-year-old female patient reported with the chief complaint of unaesthetic smile. On clinical examination the patient was diagnosed with Angle’s class I malocclusion with an ectopically erupted maxillary left canine labial to the left central incisor with retained deciduous canine. The treatment plan decided was to extract the retained deciduous canine, level and align the ectopic canine using an R-loop. The treatment for the patient was finished in 14 months and was retained using a fixed lingual retainer in the upper and lower arches.